Dihydropyrazole-Carbohydrazide Derivatives with Dual Activity as Antioxidant and Anti-Proliferative Drugs on Breast Cancer Targeting the HDAC6 - Irving Balbuena-Rebolledo; Astrid M. Rivera-Antonio; Yudibeth Sixto-López; José Correa-Basurto; Martha C. Rosales-Hernández; Jessica Elena Mendieta-Wejebe; Francisco J. Martínez-Martínez; Ivonne María Olivares-Corichi; José Rubén García-Sánchez; Juan Alberto Guevara-Salazar; Martiniano Bello; Itzia I. Padilla-Martínez (MDPI AG, 2022)
Breast cancer (BC) is the most frequently diagnosed cancer and is the second-most common cause of death in women worldwide. Because of this, the search for new drugs and targeted therapy to treat BC is an urgent and global need. Histone deacetylase 6 (HDAC6) is a promising anti-BC drug target associated with its development and progression. In the present work, the design and synthesis of a new family of dihydropyrazole-carbohydrazide derivatives (DPCH) derivatives focused on HDAC6 inhibitory activity is presented. Computational chemistry approaches were employed to rationalize the design and evaluate their physicochemical and toxic-biological properties. The new family of nine DPCH was synthesized and characterized. Compounds exhibited optimal physicochemical and toxicobiological properties for potential application as drugs to be used in humans. The in silico studies showed that compounds with -Br, -Cl, and -OH substituents had good affinity with the catalytic domain 2 of HDAC6 like the reference compounds. Nine DPCH derivatives were assayed on MCF-7 and MDA-MB-231 BC cell lines, showing antiproliferative activity with IC50 at μM range. Compound 2b showed, in vitro, an IC50 value of 12 ± 3 µM on human HDAC6. The antioxidant activity of DPCH derivatives showed that all the compounds exhibit antioxidant activity similar to that of ascorbic acid. In conclusion, the DPCH derivatives are promising drugs with therapeutic potential for the epigenetic treatment of BC, with low cytotoxicity towards healthy cells and important antioxidant activity.